Occurrence and Growth of Killer Yeasts during Wine Fermentation - Heard, G. M. (1987)
Sixteen wine fermentations were examined for the presence of killer yeasts. Killer property and sensitivity to killer action were found in isolates of Saccharomyces cerevisiae but not in isolates of Kloeckera, Candida, Hansenula, and Torulaspora spp. Several killer and killer-sensitive strains of S. cerevisiae were differentiated by colony morphology, and this property was used to monitor their growth kinetics in mixed cultures in grape juice. Killer-sensitive strains died off within 24 to 48 h during mixed-strain fermentation. Killer action was demonstrated at pH 3.0 and pH 3.5 and over the range of 15 to 25°C but depended on the proportion of killer to killer-sensitive cells at the commencement of fermentation. The dominance of killer strains in mixed-strain fermentations was reflected in the production of ethanol, acetic acid, and glycerol.